HUBUNGAN ANTARA PROFIL BERAT ORGAN MANUSIA INDONESIA DENGAN UMUR, JENIS KELAMIN, PANJANG BADAN, DAN BERAT BADAN (STUDI DI RSUP Dr. HASAN SADIKIN BANDUNG TAHUN 2008-2012 - Naomi Yosiati; Berlian I. Fitrasanti; Yoni F. Syukriani (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2012)
In forensic medicine organ weight is a standard to determine health status and supports the determination of the cause of death. This study is aimed to analyze the correlation between organ weight profiles and age, body length, body weight, and gender; and to analyze the factors that give influence most to organ weight. Data were taken from autopsy reports of Indonesian adults, from 2008 to 2012 in Dr. Hasan Sadikin Hospital Bandung. Results showed—all male organ weight are heavier than female (N=243; 174 male, 69 female). In male there are significant correlations (p